2017
DOI: 10.1139/cjes-2016-0197
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic tectonic and thermal history of the Nenana basin, central interior Alaska: new constraints from seismic reflection data, fracture history, and apatite fission-track analyses

Abstract: The Nenana basin of interior Alaska forms a segment of the diffuse plate boundary between the Bering and North American plates and is located within a complex zone of crustalscale strike-slip deformation that accommodates compressional stresses due to oblique plate convergence to the south. The basin is currently the focus of new oil and gas exploration.Integration of seismic reflection and well data, fracture data and apatite fission track analyses with regional data improves our understanding of the tectonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Journal of Geophysical Research: Solid Earth distribution (shown in cyan) of velocity models (Figures 4a and 4e-4h) that fit the data (Figures 4b-4d). Previous analysis of the Nenana Basin from well logs, gravity, and active-source seismic has mapped depth to basement below this station as~2 km depth, corresponding to Vp between 4.5 and 5.3 km/s, or Vs 2.67-3.15 km/s (Brocher et al, 2005;Dixit et al, 2017;Tape et al, 2015), which matches our result at this station. In order to analyze approximate sediment thickness from the surface across the entirety of Alaska, while accounting for potentially faster basin material at depth, we show maps to Vs 3.1 km/s across the region for both MCMC and final Vs results in Figure 8.…”
Section: 1029/2019jb018582supporting
confidence: 90%
See 2 more Smart Citations
“…Journal of Geophysical Research: Solid Earth distribution (shown in cyan) of velocity models (Figures 4a and 4e-4h) that fit the data (Figures 4b-4d). Previous analysis of the Nenana Basin from well logs, gravity, and active-source seismic has mapped depth to basement below this station as~2 km depth, corresponding to Vp between 4.5 and 5.3 km/s, or Vs 2.67-3.15 km/s (Brocher et al, 2005;Dixit et al, 2017;Tape et al, 2015), which matches our result at this station. In order to analyze approximate sediment thickness from the surface across the entirety of Alaska, while accounting for potentially faster basin material at depth, we show maps to Vs 3.1 km/s across the region for both MCMC and final Vs results in Figure 8.…”
Section: 1029/2019jb018582supporting
confidence: 90%
“…The long history of active tectonics in Alaska has led to the formation of several major basins, including the Mesozoic foreland Colville and forearc Cook Inlet Basins, Cenozoic backarc Bristol Bay Basin, and Cenozoic stepover basins, including transtensional-transpressional Bethel Basin and rift-transtensional Copper River, Nenana, Selawik, and Yukon Flats Basins (Coleman & Cahan, 2012). These basins have been previously analyzed by geological and geophysical surveys for hazard analysis (Bruhn & Haeussler, 2006;Haeussler et al, 2000), petroleum potential (Bird, 2010;Decker et al, 1988;Kirschner, 1994;Van Kooten, 2012), and relation to tectonic processes (Cole et al, 2004;Dixit et al, 2017;Moore & Box, 2016;Plafker & Berg, 1994). Our results include the first complete 3-D tomographic maps of every major basin in Alaska with high (Colpron et al, 2007) are shown as dashed black lines in (c) with terranes Arctic Alaska (AA), Yukon composite Terrane (YCT), Wrangellia composite Terrane (WCT), and southern margin composite Terrane (SMCT) labeled.…”
Section: Tectonic Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the Eocene, several hundred kilometres of dextral motion occurred on these faults, which caused block rotation accompanied by sinistral strike‐slip and normal faulting, basin development, and magmatism (e.g. Dixit, Hanks, Rizzo, McCarthy, & Coakley, ; Dusel‐Bacon, Bacon, O'Sullivan, & Day, ; Dusel‐Bacon & Murphy, ). However, there is no record that convergent motion has crossed over the Tintina Fault to the east.…”
Section: Discussionmentioning
confidence: 99%